Learning reflections in the covid-19 pandemic period (study at the Muhammadiyah educational institutions in Surabaya) - Lina Listiana (Universitas Muhammadiyah Surabaya, 2020)
Abstract.Coronavirus outbreak (Covid-19) has attacked the entire world, transmission is sorapidly to death. Futher, the impact of covid-19 pandemic is not only attack immune system, but also social life. Such as economy, culture, politic and education.. This study aims to analyze and reflect online learning activities during the Covid-19 pandemic, addressing obstacles and assessment carried out to ensure the quality of learning. The method used is a qualitative method with a descriptive analytic approach. The study in Muhammadiyah Educational Institutions is the Muhammadiyah University of Surabaya and Schools at the senior secondary level namely Muhammadiyah High Schools in the city of Surabaya amount of 8 schools.The sample respondents were lecturers, vice-principals and teachers, with 32 respondents lecturers, and 24 respondents consists of 8 vice-principals and 16 teachers. The results and discussion showed the effectiveness of the implementation of online learning with significant achievements. A reflection for educators to is to enhance their competencies in mastering digital technology, designing modern online learning with various innovations and interesting learning methods to develop students' cognitive, affective and psychomotor domains in this pandemic period. For students they have to enhance the ability of using technology so that they become better prepared to face the challenges of learning in the industrial era 4.0. For Educational Institutions it is necessary to design a curriculum to be more adaptive to extraordinary situation.The conclusion is that the implementation of online learning during the Covid-19 pandemic at Muhammadiyah University of Surabaya and High Schools in the city of Surabaya run smoothly and effectively using Moodle owned by each educationalinstitutions which was combined with several applications and platforms.